Analisis Penerapan Person-Centered Counseling dalam Layanan Bimbingan dan Konseling di Sekolah - Barida, Muya; Titing, Herman; Ramli, M.; Radjah, Carolina Ligya; Krisphianti, Yuanita Dwi; Awaliyan, Ashiela Zahra Bintan (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The person-centered counseling approach has evolved in applications ranging from nondirective, client-centered, and student-centered to people-centered approaches. This paper describes the application of person-centered counseling in guidance and counseling services. The research method used a literature study. The results of the study and analysis were synthesized using a narrative method by grouping information or data according to the objectives of the study. The results showed that in order to truly achieve effective results from the implementation of person-centered counseling, the main attitudes the counselor needs to have are conformity, unconditional positive understanding, and understanding of empathy. The results of the study can also be discussed topics in group guidance services, individual counseling, and group counseling.